CORPORATE SIZE, PROFITABILITY, LIQUIDITY AND ACCURACY OF CORPORATE INTERNET REPORTING TIME - Ahmad Juanda; Fathiya Rachmasari (Jurnal Reviu Akuntansi dan Keuangan, 2020)
This research aims to determine the effect of company size, profitability and liquidity on corporate internet reporting timeliness which is focused on manufacture companies that listed on Indonesia Stock Exchange (IDX). Population of this study uses manufacture companies that listed on IDX period 2018, which uses purposive sampling as the method to choose samples.  122 manufacture companies are selected as the samples of this research. Data analysis techniques in this research used ordinal logistic  regression that has previously been fulfilled goodness fit and parallel lines test. The result of this research is company size has a negative effect on corporate internet reporting timeliness that causes corporate internet reporting timelines of the samples companies become shorter, which means better timeliness meanwhile profitability and liquidity do not affect corporate internet reporting timeliness of samples’ companies. This study contributes to the reference related to factors that affect the timeliness of corporate internet reporting.